Analisis Kesalahan Berbahasa Tataran Morfologi pada Surat Kabar Padang Ekspres Edisi September 2024 - Vora, Mai Yendri Yuldi; Rahman, Risky Mulya; Sandi, Dio Novri; Afnita, Afnita (Paedagogie, 2026)
The purpose of this study is to describe the forms of language errors at the morphological level contained in the Padang Ekspres newspaper, September–October 2024 edition, with a focus on errors in the use of affixes including prefixes, suffixes, confixes, and affix combinations. The research method used is a qualitative descriptive method with a content analysis approach. Data collection and analysis were carried out on sentences in the education column containing morphological errors, then analyzed based on Wibowo's (2013) morphological theory. The results of the study show four types of affixation errors, namely 15 data in the use of prefixes including the prefixes me(N)-, di-, be(R)-, and se-; 8 data in the use of suffixes including the suffixes {-kan}, {-i}, and {-nya}; 2 data in the use of confixes, namely {ke-an} and {peN-an}; and errors in the use of affix combinations amounting to 2 data, including {me-kan} and {me-i}. Overall, 27 language errors were found at the morphological level. The conclusion of the study shows that the use of Indonesian in print media is still not fully in accordance with standard morphological rules, so that the results of this study can be used as evaluation material for journalists and editors to improve language accuracy in reporting